A rod‐like mesoporous carbon derived from agro‐industrial cassava petiole waste for supercapacitor application. Issue 3 (13th October 2020) - Taer, Erman; Apriwandi, Apriwandi; Dalimunthe, Bima Kumala Levanadea; Taslim, Rika
Abstract: BACKGROUND: Agro‐industrial co‐products rich in lignocellulose, for example cassava petiole (CP) waste, have high potential as sources of porous carbon materials, alongside other impressive advantages, including ease of acquisition, abundance and availability, renewability and low cost. This work shows the successful treatment of mesoporous carbon with rod‐like structure derived from agro‐industrial CP waste carbonized and physically activated by direct one‐stage integrated pyrolysis using a zinc chloride (ZnCl2 ) activator agent, in the production of a supercapacitor electrode for energy storage. The ZnCl2 was tested at varying concentrations, including 0.5, 0.7 and 0.9 mol L –1 . The surface morphology, chemical content, surface area and porous size distribution were evaluated to determine the physical properties of activated carbon, and a cyclic voltammetry method was used to assess the electrochemical characteristics using a two‐electrode system in 1 mol L –1 H2 SO4 as an electrolyte. RESULTS: The porous carbon obtained displayed a rod‐like morphology structure, featuring numerous hierarchical tuneable and well‐confirmed micropores and mesopores. This monolithic material contained predominantly C (87.85%), demonstrating a maximum surface area of 759.816 m 2 g −1 at 0.9 mol L –1 concentration. Furthermore, the highest specific capacitance reached was 193 F g −1 at 0.7 mol L –1, with maximum energy and power densities of 26.90 Wh kg −1 and 96.94 W kg −1, respectively. CONCLUSION: The novel rod‐like mesoporous carbon derived from CP waste produced using a facile, cost‐effective and sustainable method, without metal–organic framework or templates, shows great potential as an electrode material for enhanced supercapacitor performance. © 2020 Society of Chemical Industry (SCI)